Complementary molecular shapes and additivity of the packing parameter of lipids. - Kumar, V V (1991)
Physical dimensions of a membrane component influence its phase preference upon hydration. A dimensionless packing parameter, S, given by S = V/al, where V is the hydrocarbon volume, a is the area of the head group, and l is the critical length of the hydrocarbon chain, is useful in determining the phase preference of a lipid, and the value of S usually lies between 0.5 and 1 for bilayers. Here, the value of S is calculated for phosphatidylcholine (PC) and lysophosphatidylcholine (lysoPC) as a function of chain length, and it is shown that diacylPC having an S value of less than 0.74 does not form bilayers. For example, diacylPC, up to a chain length of eight carbon atoms, forms only micelles, whereas higher homologs with S greater than 0.74 form bilayers. It is also shown that when lipid molecules having complementary shapes associate, the value of S becomes additive. Using the additivity of S, a number of experimental results for lipid mixtures can be explained. For example, lysoPC and cholesterol form lamellar structures between 45 and approximately 80 mol% cholesterol, and the additive value of S for this region is between 0.74 and 1. Similarly, the additivity of S shows that the maximum amount of cholesterol that can be incorporated into PC bilayers is 50 mol%, in agreement with experimental studies.